Benzoate fraction from Gentiana rigescens Franch alleviates scopolamine-induced impaired memory in mice model in vivo. (4th December 2016) - Li, Jing; Gao, Lijuan; Sun, Kaiyue; Xiao, Dan; Li, Wanyi; Xiang, Lan; Qi, Jianhua
Abstract: Ethnopharmacological relevance: G. rigescens Franch (Long Dan Cao in Chinese) is a well-known TCM herb. It is clinically used with other drugs for the treatment of brain diseases such as epilepsy, postherpetic neuralgia in China. Aim of study: In our previous study, the 11 dihydroxybenzoates compounds with NGF mimicking activity from G. rigescens Franch were found. In the present study, the neurogenesis and neuroprotection of a mixture of benzoates ( n-GS) were investigated in animal level. Materials and methods: The NGF mimicking activity of n-GS from G. rigescens Franch was examined in PC12 cells. The neurogenesis effects of n-GS were investigated in ICR mice with 5-bromo-2-deoxyuridine (BrdU) and neuronal neclei (NeuN) double immunostaining. Furthermore, the neuroprotection effects of n-GS on the memory in a scopolamine (SCO)-induced mouse model were evaluated with animal behavior tests. Results: The NGF-mimicking function and neurogenesis of n-GS were observed in PC12 cells and in normal mice. Subsequently, we investigated the effects of n-GS on the memory in a SCO-induced mouse model. In Y-maze test, SCO significantly lowered the alternation. This finding was reversed by n-GS and donepezil (DONE). SCO significantly impaired the mice's performance in novel object recognition (NOR) and Morris water maze (MWM) tests. The time spent to explore the novel object was longer in the n-GS- and DONE-treated groups than in the SCO control group. In the MWM test, the escape latency of n-GS- and DONE-treated groups was shorter than that of the SCO control group. Mechanism study showed that SCO significantly reduced superoxide dismutase (SOD) but increased the activities of acetylcholinesterase (AChE) and the levels of malondialdehyde (MDA) in the hippocampus and cerebral cortex, which all can be improved by n-GS and DONE. Additionally, the phosphorylation of type 1 insulin-like growth factor (IGF-1) receptor, extracellular signal-regulated kinase (ERK), and cAMP responsive element-binding (CREB) protein in the hippocampus was significantly up-regulated in the treatment group compared with that in the SCO group. Conclusions: n-GS could alleviate impaired memory of the SCO-induced mice model by inhibiting AChE activity and oxidative stress, and regulating the IGF-1R/ERK signaling pathway. Graphical abstract: